Influência de um novo produto fermentado de soja sobre o metabolismo lipídico tecidual em ratos submetidos a uma dieta enriquecida com colesterol - Viana, Fabiana Pavan (Universidade Federal de São Carlos, 2005)
In relation to many types of diets, soybean has been researched as a possible cohelping resource in the treatment of diverse pathologies. Therefore, the objective of this current work was to investigate the manifestation of a new soybean fermented product with added Enteroccocus Faecium and Lactobaccilus Jugurti on the lipid metabolism of male Wistar rats, aged approximately 3 months and weighing between 220-240 grams. They were divided into four experimental groups and treated with different types of diets: Standard diet C; Standard diet associated to the fermented product CPF 1ml/day/rat); Hypercholesterolemic diet associated to the Fermented Product HPF; Hypercholesterolemic diet H. The rats were maintained sedentary throughout the entire experimental period. After 08 weeks of treatment they were slaughtered, separating and weighing the plasma, the white retroperitoneal adipose tissues RET and epididimal EPI, the brown interescapular adipose tissue TAM, gastrocnemic muscle GAST and liver FIG. These were stored in a freezer at -20oC for biochemical and morphological analysis. The results demonstrated that the soybean fermented product diminished body weight gain in rats submitted to the high rate cholesterol diet as well as the standard diet. Most of the evidence proved that the soybean fermented product diminished the lipid synthesis, adipose areas and diameter, increased lipololysis, diminished the fat content (in some situations) and the RET and EPI adipose tissues, mainly when the animals were submitted to a hypercholesterolemic diet. Furthermore, it was observed that this product reduced the fat content, lipid synthesis and FIG weight, even when the animals were submitted to a high rate cholesterol diet. Another effect that was observed of the soybean fermented product was the diminishing of the fat content in GAST. Moreover, when the product was administered in the hypercholesterolemic group, it increased the fat content and reduced the lipid synthesis in TAM in relation to the H group. It can be suggested that administering the soybean fermented product can be a possible co-helper in reducing adiposity, in preventing hepatic esteatosis and in controlling body weight.
Keywords: Lipídios - metabolismo; Produto fermentado de soja; Enterococcus faecium; Lipólise; Lipogênese; Lipolitic; Lipogenesis; Collecting lipids of diet; Obesity; Soybean; Enterococcus faecium; Lactobaccilus jugurti; CIENCIAS BIOLOGICAS::FISIOLOGIA